ANALYSIS ABOUT THE PERPETUATION OF CRIME IN IMPOVERISHED COMMUNITIES - Madalozzo da Rosa, Gilmar; Palheta dos Santos, Fabrício (Revista Gênero e Interdisciplinaridade, 2025)
This article aims to analyze the criminalization of poverty and the cycle of criminality embedded within poor populations. The Federative Republic of Brazil has one of the highest inequality rates in the world, despite its Federal Constitution providing for fundamental objectives such as building a free, just, and solidary society; eradicating poverty and marginalization, and reducing social and regional inequalities; as well as promoting the well-being of all, without prejudice of origin, race, sex, color, age, and any other forms of discrimination. It is precisely in these discriminations that the country structurally reaches precarious levels. The penalization of poverty establishes a cycle of criminality that condemns the poorest for monetary, social, cultural, racial, and even intellectual aspects. The precarious living conditions faced by the population inhabiting segregated communities like favelas, due to the lack of health, education, security, housing, and many other fundamental rights assured, especially by the Federal Constitution, are utopian. In light of this reality, the consequences are disastrous. The disorderly and unsupported growth of these areas creates conflicting social spaces, which become focal points for violent activities. In this context, crime is a direct result of the lack of basic rights that are denied daily.